ANALISIS UNSUR-UNSUR SISTEM PENGENDALIAN INTERNAL ASET TETAP TERHADAP PENGAMANAN PELAPORAN ASET DAERAH PADA PEMERINTAH PROVINSI SUMATERA SELATAN - M.Thoyib; Prima Fathur Rahman; Indra Satriawan (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2021)
The purpose of this study was to analyze the effect of organizational structure, authorization system, recording procedures, healthy practices partially and simultaneously on the security of reporting regional assets in regional organizations of South Sumatra Province, as well as to fulfill one of the requirements in completing studies at the Sriwijaya State Polytechnic. The data used are primary data. The sample selection technique is purposive sampling. The sample of this study amounted to 80 respondents who occupied the positions of agency head, agency secretary, head of the budget department, head of accounting at regional organizations in South Sumatra Province. The data obtained were analyzed using descriptive analysis, classical assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing with the help of SPSS software version 24. The results showed partially the organizational structure, authorization system, recording procedures, and healthy practices had a positive and significant impact on the security of regional asset reporting. Organizational structure , authorization systems, recording procedures and sound practices simultaneously have a significant effect on the security of regional asset reporting.